Nora M. Alter and Timothy Corrigan. Essays on the Essay Film. Columbia UP, 2017. - Angelica Fenner (Studies in 20th & 21st Century Literature, 2019)
Review of Nora M. Alter and Timothy Corrigan. Essays on the Essay Film. Columbia UP, 2017. 371 pp.
Keywords: Essay Film; Critical Theory; Genre; Media Theory; Experimental Film and Video